PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DI KELAS V SDN 107/II DANAU BULUH - Ucci Erianti; Nurlev Avana; Iri Hamzah (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
The study demonstrates a significant and progressive improvement. During the initial intervention phase (Cycle I), the Example Non-Example model facilitated the achievement of the established learning mastery standard for half of the student cohort (50%). This outcome provided a foundational baseline, indicating the model's inherent potential. Nevertheless, the model's efficacy was more definitively affirmed by the results of Cycle II. Subsequent to a period of reflection and strategic refinement based on the first cycle's findings, a substantial increase was observed as the student mastery percentage surged to 80%. This figure serves as tangible evidence that the learning model, upon adaptation and optimization, is a highly valid solution for overcoming the specific issue of low learning achievement that was previously meticulously identified in the fifth-grade class at SDN 107/II Danau Buluh.